2017
DOI: 10.1021/acs.joc.7b01541
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Cascade Approach toward 2-Alkoxy/2-Sulfenylpyridines and Dihydrofuro[2,3-b]pyridines by Trapping In Situ Generated 1,4-Oxazepine

Abstract: An efficient cascade reaction via trapping in situ generated active intermediate 1,4-oxazepine, formed from base-promoted 7-exo-dig cyclization reaction of N-propargyl enaminone, has been developed. Alcohols/thiols and aldehydes were used as trapping agents, providing 2-alkoxy/2-sulfenylpyridines and dihydrofuro[2,3-b]pyridines in moderate to high yields. This cascade reaction was completed within 30 min at room temperature, generating 1 equiv of HO as the sole byproduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…[25] Finally, with stoichiometric amounts of ZnCl 2 , the cyclization leads to the 7-membered ring 1,4-oxazepines. [26] Apart from the metal-catalyzed protocols, upon treatment with a base in the presence of a suitable nucleophile or electrophile, N-propargyl enaminones lead to substituted pyridines, [27] but not to 3-keto pyridines, as in our case.…”
mentioning
confidence: 68%
“…[25] Finally, with stoichiometric amounts of ZnCl 2 , the cyclization leads to the 7-membered ring 1,4-oxazepines. [26] Apart from the metal-catalyzed protocols, upon treatment with a base in the presence of a suitable nucleophile or electrophile, N-propargyl enaminones lead to substituted pyridines, [27] but not to 3-keto pyridines, as in our case.…”
mentioning
confidence: 68%
“…In 2017, they also reported alcohols and thiols were also adopted as nucleophiles, thereby providing similar products via consecutive 6π‐electrocyclization and walk rearrangement processes (Scheme a) . Moreover, Cui and Zhang's groups simultaneously reported terminal carbon of N‐propargyl enaminones could also be used as nucleophiles to trap extern aryl aldehydes or N‐sulfonyl imines, providing pyridine‐fused heterocycles ,. Encouraged by above achievements, we wondered whether 1,4‐benzoxazepine could also be used as reactive intermediate to induce new cascade reactions.…”
Section: Figurementioning
confidence: 99%
“…They also found that N‐based nucleophiles could be in situ generated from N‐propargyl enaminones and trapped by 1,4‐oxazepines . In 2017, they also reported alcohols and thiols were also adopted as nucleophiles, thereby providing similar products via consecutive 6π‐electrocyclization and walk rearrangement processes (Scheme a) . Moreover, Cui and Zhang's groups simultaneously reported terminal carbon of N‐propargyl enaminones could also be used as nucleophiles to trap extern aryl aldehydes or N‐sulfonyl imines, providing pyridine‐fused heterocycles ,.…”
Section: Figurementioning
confidence: 99%
“…Chalcones transformation might proceed either by 1,4-addition or 1,2-addition. Examples of heterocyclic compounds from chalcones are pyrazoles [1,2], pyrroles [3][4][5], pyrazoline [6], isoxazoles [7][8][9], pyrimidines [10,11], pyridines [12][13][14][15][16], indoles, indazoles, triazoles [17,18], imidazoles [19,20], thiazines [21], 1,5-benzodiazepines, 1,3,4-thiadiazepines, benzoazepines, and 1,5-benzodiazepines [22]. Chalcones are multifunctional molecules that possess promising pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…-b]pyridines 72[15]. While Abd El-Sattar et al reported pyridine 74 from chalcone 73 and malononitrile[16] (Scheme 12).…”
mentioning
confidence: 99%